Cytomegalovirus-Specific T Cells from Third-Party Donors Successfully Treated Refractory Cytomegalovirus Retinitis after Unrelated Umbilical Cord Blood Transplantation. (15th November 2022) - Li, Na; Sun, Guangyu; Zhu, Lihua; Ding, Kang; Liu, Huilan; Zhu, Xiaoyu; Tang, Baolin; Yao, Wen; Wan, Xiang; Geng, Liangquan; Qiang, Ping; Song, Kaidi; et al.
Abstract : Umbilical cord blood (UCB) transplants (UCBTs) are becoming increasingly common in the treatment of a variety of hematologic and nonhematologic conditions. The T cells from UCB are naïve T cells, which have not yet been exposed to antigens and therefore do not contain T cells with specific immune functions against viruses. Cytomegalovirus (CMV) infections occur in more than 80% of patients after UCBT compared to other types of transplantation. Anti-CMV medications are currently restricted, with ganciclovir, foscarnet, and valganciclovir being the most common in China; however, with limited efficacy and considerable side effects, all these drugs are susceptible to viral resistance. In recent years, cytomegalovirus-specific T cells (CMVST) have advanced the treatment of viral infections in immunodeficient patients. CMVST usually uses the same donor as hematopoietic stem cell transplantation. CMVST should be administered to UCBT patients because of the absence of donors after UCBT. In China, there is no report on the use of CMVST to treat CMV infection after UCBT, and foreign reports are also limited. This paper reported a 20-year-old male patient with acute myeloid leukemia who developed cytomegalovirus retinitis (CMVR) after umbilical cord blood transplantation. After ineffective viral treatment, he was treated with a third-party donor CMVST and was successfully transformed into CMV nucleic acid negative.